Potential Cytotoxic Effect of Crude Extract Produced by Lactobacillus spp on Caco-2 & L20B Cell Lines in vitro - Yahia, Jenan Salih (Iraqi Journal of Cancer and Medical Genetics, 2017)
This study was designed to determine the cytotoxic effect of crude products which was produced by isolates of Lactobacillus spp against three cell lines using 3-(dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide (MTT assay). About 72 samples were collected from local dairy products and infant feces with age of (1- 40 days) in Baghdad, the collection of those samples last long (September 2016 to January 2017). All isolates were identified as Lactobacillus spp according to their morphological, cultural, biochemical features and PCR technique by 16SrRNA gene. The cytotoxicity of crude extract was evaluated on cancer intestinal cells of mice L20B, human colon adenocarcinoma Caco-2 and human hepatic WRL-68 cell lines. The results showed that crude extract had cytotoxic effect on L20B with IC50= 17 g/ml and on Caco-2 with IC50=221.9 g/ ml in concentration 400 g/ml for both. While the crude extract of WRL-68 cells did not show when treated with the same concentration when used WRL-68 as normal cells for comparison. Conclusion: In last years, the high prevalence rate of many types of cancer in Baghdad, especially of intestinal cancer in human, so had used materials was produced by Probiotic bacteria to study their effects on the cancer cells in vitro. Key words: MTT assay, Caco-2 cell line, L20B cell line, Crude extracts, Lactobacillus spp.